PENGELOLAAN PASRAMAN DI SD NO.1 DARMASABA DALAM MENINGKATKAN SRADHA DAN BHAKTI SISWA - Ni Kadek Supadmini; I Komang Wisnu Budi Wijaya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This reaearch aims to identify management patterns in SD No 1 Darmasaba in order to improve student’s Sradha and Bhakti. This research is classified into qualitative research. Sources of The research data sources from thePasraman manager, Pasraman activity documents and Hindu literature texts. The data collection method were carried out by observations, interviews and literature. The research instrument that used was observation sheets and interview guidelines. Collected data was analyzed using descriptive analysis techniques. Theresult of the research stated that the Pasramanmanagement in SD No.1 Darmasaba used the POAC pattern, namely Planning, Organizing, Actuation, and Supervision. In implementing this pattern, various parties are involved, for example, Pasraman managers, teachers, school committees, and student’s parents.